Specialization in Production and the Production Possibility Locus - McKenzie, Lionel W. (Review of Economic Studies, 1955)
Journal Article Specialization in Production and the Production Possibility Locus Get access Lionel W. McKenzie Lionel W. McKenzie Durham, North Carolina Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 23, Issue 1, 1955, Pages 56–64, https://doi.org/10.2307/2296152 Published: 01 April 1955